Women and authority in early modern Spain the peasants of Galicia - Poska, Allyson M. (Oxford University Press, 2005)
Allyson Poska examines the social and economic significance of the peasant women of Galicia, using archival documentation. She focuses on how the women perceived and asserted their authority within the family and how a large number of female-headed households functioned in the absence of men.